Histomorphometric changes in the vessel wall at the site of amputation in diabetic patients--do they influence healing of the stump? - Naidu, S.V.L.G.; Sengupta, S. (2005)
Intimal thickening and medial thinning in the arteries can be used to predict the stump healing in patients who underwent below-knee amputation. For ray amputation patients, similar changes occurred in the dorsal veins, and this finding can also be used to predict the healing of the stump. However, intimal thickening occurred at the expense of the media; therefore, there is little change in the wall thickness.